Evaluation of total purchasing pilots in England and Scotland and implications for primary care groups in England: personal interviews and analysis of routine data. Issue 7153 (25th July 1998) - Goodwin, Nicholas; Mays, Nicholas; McLeod, Hugh; Malbon, Gill; Raftery, James
Abstract: Objectives : To evaluate the reported achievements of the 52 first wave total purchasing pilot schemes in 1996-7 and the factors associated with these; and to consider the implications of these findings for the development of the proposed primary care groups. Design : Face to face interviews with lead general practitioners, project managers, and health authority representatives responsible for each pilot; and analysis of hospital episode statistics. Setting : England and Scotland for evaluation of pilots; England only for consideration of implications for primary care groups. Main outcome measures : The ability of total purchasers to achieve their own objectives and their ability specifically to achieve objectives in the service areas beyond fundholding included in total purchasing. Results : The level of achievement between pilots varied widely. Achievement was more likely to be reported in primary than in secondary care. Reported achievements in reducing length of stay and emergency admissions were corroborated by analysis of hospital episode statistics. Single practice and small multipractice pilots were more likely than large multipractice projects to report achieving their objectives. Achievements were also associated with higher direct management costs per head and the ability to undertake independent contracting. Large multipractice pilots required considerable organisational development before progress could be made. Conclusion : The ability to create effective commissioning organisations the size of the proposed primary care groups should not be underestimated. To be effective commissioners, these care groups will need to invest heavily in their organisational development and in the short term are likely to need an additional development budget rather than the reduction in spending on NHS management that is planned by the government.